IF you can keep your head: The unintended consequences of the Impact Factor on tourism research - Poria, Y.; Schwartz, Z.; Uysal, Muzaffer (Pergamon, 2015)
The growing importance of academic journals' Impact Factor (IF) is reshaping the research arena. In this paper we discuss the possible impact of the IF on tourism research and on key players such as editors of top-tier tourism journals, students, researchers as well as directors of tourism academic units. It also examines the impact on the public whose funds make up part of scholars' salaries and, to some extent, research grants. It is argued here that by encouraging researchers to target only journals with a high IF, research may come to a standstill, as exploratory, industry-related or critical studies may cease being conducted and published. This is a call to minimize the reliance on the IF and its glorification as an indicator of research quality and researchers' performance.